El consejero entrenado profesionalmente aporta una nueva dimenension a la rehabilitación - Stubbins, Joseph (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present paper describes the profession of Rehabilitation Counselling and the work the Peruvian Institute for Rehabilitation in Lima does for the dis- abled. The Rehabilitation Counsellor works in dose connection with doctors, psychiatrists, occupational therapists, social workers and other psychologists. The patient’s eligibility for treatment is determined by means of an interview, medical reports and other information. Through psychological and vocational tests, a vocational evaluation is per formed and the patient is located at a controlled work center where he can be observed by the counsellor. The most difficult part of the counsellor’s job is the achievement of permanent employment for his patient and in getting civic leaders’ and businessmen’s attention and cooperation to create job opportunities for the disabled. The final practice is "following-up”, that is, keeping in contact with the patient once the agency services are over. Rehabilitation counselling offers young people with a creative mind a professional field with a great deal of freedom for personal goals and methods of work.